2004
DOI: 10.1007/s00264-003-0510-5
|View full text |Cite
|
Sign up to set email alerts
|

Glove punctures in orthopaedic surgery

Abstract: From February 2001 to May 2001, 792 latex gloves used in 100 operations from three orthopaedic sub-specialties (paediatrics, hand and spine) were tested for puncture by a water infusion test. Sixty-nine gloves from 45 operations were punctured, giving an overall glove perforation rate of 8.7% (69/792) and an operative perforation rate of 45% (45/100). The hand operations had the lowest operative perforation rate (19.4%) while the spine operations had the highest (63.6%). The glove perforation rate increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
1
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 9 publications
5
48
1
13
Order By: Relevance
“…In their study, perforation was observed in 15.4% of gloves during the first 90 minutes of orthopaedic procedures and this increased to 18.1% if the glove was worn between 91 to 150 minutes, and to 23.7% if the glove was worn longer than 150 minutes [16]. Limited data are available regarding risk of compromise of glove integrity in specific orthopaedic procedures [1,2,4,6,8,9,20]. At least one glove was found to be perforated in 39% of TKAs, with a perforation incidence of 4.29% of the gloves worn in these procedures [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, perforation was observed in 15.4% of gloves during the first 90 minutes of orthopaedic procedures and this increased to 18.1% if the glove was worn between 91 to 150 minutes, and to 23.7% if the glove was worn longer than 150 minutes [16]. Limited data are available regarding risk of compromise of glove integrity in specific orthopaedic procedures [1,2,4,6,8,9,20]. At least one glove was found to be perforated in 39% of TKAs, with a perforation incidence of 4.29% of the gloves worn in these procedures [8].…”
Section: Discussionmentioning
confidence: 99%
“…The use of power tools, handling sharp bone, and working in deep cavities all influence the risk of glove perforations in orthopaedic surgery [20]. Double gloving has been recommended in orthopaedic procedures to ameliorate the risk of perforation but compliance is not universal [7,18].…”
Section: Introductionmentioning
confidence: 99%
“…Glove perforation during any surgical procedure is of concern because it increases the risk of disease transmission to both the patient and medical personnel as well as contamination of the surgical field. Several studies have reported the incidence of glove perforation during orthopedic procedures to be between 3.6% and 26% [11][12][13][14][15][16][17][18]. Prior studies have demonstrated an association between glove perforation and duration of the procedure, hand dominance, and specific portions of the procedure [11,12,14,19].…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the unsettling mere prospect that these highly regarded modern medical tools of quality and safety may fail to fulfill their intended purpose, the prevalence of surgical glove perforation has been reported to be as high as 43%-64% [10,14]. Even more disturbing, up to 73% of perforations are not recognized until the completion of the surgical procedure [11].…”
Section: T He German Surgeon Paulmentioning
confidence: 99%
“…These perforations usually involve the gloves of the operating surgeon (77%), but surgical assistants (13%), and scrub nurses (10%) are also at risk [4]. Furthermore, the risk of glove perforations appears to increase with increased duration of a surgical procedure [3,9,14], in bony versus soft-tissue procedures [14], and during the manipulation of complex instrumentation or implants in deep wounds [10]. There are good data to suggest that double gloving may prevent the complete loss of this protective barrier [6]; however, utilizing double gloves, alone, does not reliably prevent both outer and inner glove perforations [14].…”
Section: T He German Surgeon Paulmentioning
confidence: 99%